2002
DOI: 10.1023/a:1020228723299
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Novel homodinuclear Cu(II) (K1), heterodinuclear Cu(II)-Mn(II) (K2) and homotrinuclear Cu(II) (K3) complexes with a novel oxime-type ligand have been prepared and their nucleolytic activities on pCYTEXP were established by neutral agarose gel electrophoresis. The analyses of the cleavage products obtained electrophoretically indicate that although the examined complexes induces very similar conformational changes on supercoiled DNA by converting supercoiled form to nicked form than linear form in a sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…It has been proven that some reactive oxygen species, such as hydroxyl radicals, may be produced during the reactions of metal complexes with DNA, and these reactive oxygen species may be responsible for the oxidative DNA cleavage. It is well known that high pH conditions may be favorable for the formation of such reactive oxygen species [25,26]. …”
Section: Effects Of Ph On Plasmid Dna Cleavagementioning
confidence: 99%
“…It has been proven that some reactive oxygen species, such as hydroxyl radicals, may be produced during the reactions of metal complexes with DNA, and these reactive oxygen species may be responsible for the oxidative DNA cleavage. It is well known that high pH conditions may be favorable for the formation of such reactive oxygen species [25,26]. …”
Section: Effects Of Ph On Plasmid Dna Cleavagementioning
confidence: 99%
“…The cytotoxicity of the novel complex was examined in NRK-52E rat renal tubular cells and HepG2 human hepatoma cells, and the results indicated that the trans-platinum complex caused death by apoptosis, making the complex potentially suitable for therapeutic purposes. Furthermore, oxime molecules were selected as new ligands, not only because water solubility could be augmented for the platinum derivatives, but also because of their biological effects, such as endothelium independent relaxation in blood vessels [24], oxidative DNA cleavage [25], an increase in the targeting of specific nuclear bases of DNA [26], and a change in the antitumor action [27]. Additionally, some trans-Pt complexes with isopropylamine ligand have been studied that they exhibited higher activity in tumor cell lines which are sensitive and resistant to cisplatin [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the transition metals play a very important role in organism and their complexes can interact non-covalently with nucleic acid by intercalation, groove-binding or external electrostatic binding for cations [3,[7][8][9][10][11]. And that many transition metal complexes have been investigated to be utilized as probes of DNA structure, agents for mediation of strand scission of duplex DNA and chemotherapeutic agents [12][13][14]. Most notably, some Pt(2þ) complexes (cisplatin and carboplatin) have found their way into the pharmaceutical armamentarium as applied clinical antitumor drugs [15].…”
Section: Introductionmentioning
confidence: 99%